A thermal radiation exchange model of whole-body UV phototherapy. (24th August 2020) - Coleman, A J; Aneju, G A; Freeman, P; Fedele, F
Abstract: A novel model of the skin dose in whole-body UV phototherapy treatment cabins is presented. The model is based on an analysis of the thermal radiation exchange between two surfaces, in this case the UV source and the patient. It is shown to allow analytical treatment of the multiple internal reflections in a treatment cabin that account for around 40% of the skin irradiance. The model provides predictions of the absolute irradiance at the skin and shielding factors in seven different UVA and NB-UVB cabins that are within 6% of those measured using a calibrated radiometer and within 12% for all nine cabins. The model predicts reducing skin irradiances with increasingly patient size, a trend demonstrated in clinical measurements. The exact sensitivity to patient size in automated cabin dosimetry systems, however, varies with in-built sensor positioning. The potential to extend the use of the model to investigate improved design of automated dosimetry systems is discussed.